avoid all that gibberish by just typing:
x^2 - x - 3/4 = 0
let's complete the square:
x^2 - x + ... = 3/4 + ...
x^2 - x + 1/4 = 3/4 + 1/4
(x - 1/2)^2 = 1
x - 1/2 = ± 1
x = 1+1/2 or x = -1+1/2
x = 3/2 or x = -1/2
you decide what to do with my answer, (which is correct for the given equation)
Use the work shown to find the solutions of the quadratic equation.
x2 – x – StartFraction 3 Over 4 EndFraction = 0
x2 – x = StartFraction 3 Over 4 EndFraction
x2 – x + (StartFraction 1 Over 2 EndFraction) squared = StartFraction 3 Over 4 EndFraction + (StartFraction 1 Over 2 EndFraction) squared
x2 – x + StartFraction 1 Over 4 EndFraction = StartFraction 3 Over 4 EndFraction + StartFraction 1 Over 4 EndFraction
Which is a solution of x2 – x – StartFraction 3 Over 4 EndFraction = 0?
1 answer